Brian's Return : Brian$1 (Bs Sagas #4 - Paulsen, Gary (New York : Scholastic, 1999)
After having survived alone in the wilderness, Brian finds that he can no longer live in the city but must return to the place where he really belongs.
Keywords: Self-reliance -- Fiction; Wilderness areas -- Fiction; Wilderness survival -- Fiction